Language and Time: interaction and development (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article to the range of issues related to the functioning of language in society in the context of a single time dimension is devoted. The linguistic phenomena caused by changes in the world last period are analyzed, the linguistic aspect of the incompleteness of culture of the late XX – early XXI century is disclosed, observations on the language of art works are made.
Keywords: the language of the time; society; social time; the origin of languag; normalization